Psychological Challenges Faced by Mothers of Children with Congenital Heart Disease: A Mixed-Methods Study at a Tertiary Care Hospital - Thillainayaki Chandran; Theranirajan Ethiraj; Shankar Shanmugam Rajendran; Kannan Kasinathan; Johnson Chinnadurai; Baby Ilavarasi Chakkaravarthi; Rathiswari Posan (Journal of Pharmacy and Bioallied Sciences)
Introduction: Congenital heart disease (CHD) is a chronic condition caused by structural heart defects, impacting children’s health across ages. The emotional distress experienced by mothers of children with CHD is profound, including anxiety, depression, stress, and grief. Understanding these emotional challenges is crucial for developing appropriate support systems for affected families. Methodology: This study employed a mixed-methods approach, using purposive sampling to select five mothers of children with CHD. Data collection was done through in-depth interviews following a phenomenological design. The interviews covered emotional responses to diagnosis, coping mechanisms, family impacts like sleep deprivation, and sources of support such as prayer and healthcare professionals. Results: The results revealed that mothers scored high for depression at 60.48% and moderate stress at 56.86%. Anxiety was relatively lower, with an average score of 49.43%. Family members experienced emotional strain and sleep deprivation due to the demands of managing a child’s chronic health condition. The support received from healthcare providers and social media was crucial. Conclusion: The findings underscore the severe emotional burden on mothers of children with CHD, with significant levels of depression and stress. While anxiety levels were lower, other emotional factors like grief and fear played a major role. Support mechanisms such as medical care and online communities were helpful but not sufficient. Targeted interventions to reduce emotional distress and improve mental health are essential for these mothers and their families.